2020
DOI: 10.7554/elife.60827
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of elevated proton leak rejuvenates mitochondria in the aged cardiomyocyte

Abstract: Aging-associated diseases, including cardiac dysfunction, are increasingly common in the population. However, the mechanisms of physiologic aging in general, and cardiac aging in particular, remain poorly understood. Age-related heart impairment is lacking a clinically effective treatment. Using the model of naturally aging mice and rats, we show direct evidence of increased proton leak in the aged heart mitochondria. Moreover, our data suggested ANT1 as the most likely site of mediating increased mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 59 publications
3
44
0
Order By: Relevance
“…This pathological proton leak is associated with inefficient ATP synthesis and increased electron flux and oxygen consumption, increasing ROS production and mPTP sensitivity. Interestingly, the treatment with the drug SS-31, a tetrapeptide that binds to cardiolipin-containing membranes and improves membrane stability and cristae curvatures ( Birk et al, 2014 ), arrested proton leak, restored mitochondrial functionality, reduced ROS production and more surprisingly rejuvenated old cardiomyocytes ( Zhang et al, 2020 ). Cardiac aging is characterized by a decrease in the number of mitochondria in the heart and a reduction in the area of the inner mitochondrial membrane implicating OXPHOS at the center of cardiac mitochondrial metabolism deficiency during aging.…”
Section: Cardiac Mitochondria In Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathological proton leak is associated with inefficient ATP synthesis and increased electron flux and oxygen consumption, increasing ROS production and mPTP sensitivity. Interestingly, the treatment with the drug SS-31, a tetrapeptide that binds to cardiolipin-containing membranes and improves membrane stability and cristae curvatures ( Birk et al, 2014 ), arrested proton leak, restored mitochondrial functionality, reduced ROS production and more surprisingly rejuvenated old cardiomyocytes ( Zhang et al, 2020 ). Cardiac aging is characterized by a decrease in the number of mitochondria in the heart and a reduction in the area of the inner mitochondrial membrane implicating OXPHOS at the center of cardiac mitochondrial metabolism deficiency during aging.…”
Section: Cardiac Mitochondria In Agingmentioning
confidence: 99%
“…The Telomerase Activator 65 (TA-65), a compound extracted from Astragalus membranaceus has been also shown to extend lifespan by increasing TERT expression and reducing markers of cardiovascular disease and inflammation ( Fernandez et al, 2018 ). The tetrapeptide SS-31 binds to cardiolipin from the inner mitochondrial membrane, stabilizing membranes and the integral membrane mitochondrial proteins, in particular, ANT protein to prevent and even revert aging-associated mitochondrial dysfunction in cardiomyocytes ( Szeto, 2006 ; Birk et al, 2014 ; Zhang et al, 2020 ). Finally, the thiazolidinedione pioglitazone has been shown to be a potent inductor of the PGC-1α, mitochondrial biogenesis and antioxidant mitochondrial defense ( Bogacka et al, 2005 ; Butterick et al, 2016 ).…”
Section: Mitochondrial Therapies For a Healthy Heartmentioning
confidence: 99%
“…One mechanism by which elamipretide achieves this effect is by modifying PTM profiles, including enhanced cMyBP-C phosphorylation and decreased global S-glutathionylation (Chiao et al, 2020). These changes are likely secondary to its primary effect of associating with the cardiolipin-rich mitochondrial inner membrane where it improves the efficiency of the electron transport chain and other mitochondrial proteins and reduces the leak of reactive species (Campbell et al, 2019;Chavez et al, 2019;Mitchell et al, 2020;Whitson et al, 2020;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies with isolated mitochondria and cell cultures show that SS-31 improves electron transfer efficiency and increases ATP production while reducing electron leak and reactive oxygen species (ROS) production (3)(4)(5)(6)(7). Furthermore, animal studies have demonstrated the ability of SS-31 to maintain cellular bioenergetics under stress conditions such as ischemia, hypoxia, and agingrelated dysfunction (8)(9)(10)(11). Finally, the clinical efficacy of SS-31 has been demonstrated for primary mitochondrial disorders (12,13) and for age-related chronic diseases associated with mitochondrial dysfunction (14).…”
Section: Introductionmentioning
confidence: 99%
“…Based on a crosslinking/mass-spectrometry approach with a biotinylated SS-31 variant, the SS-31 interactome was shown to include a subset of membrane complexes primarily involved in ATP-generating processes (19). Moreover, in aged cardiomyocytes, SS-31 was shown to reduce proton leak mediated by the adenosine nucleotide transporter (ANT1) and stabilize the ATP synthasome (11). Notably, the vast majority of these SS-31-interactive proteins are known to bind CL, supporting a role of mitochondrial lipid composition in the molecular interactions of these compounds.…”
Section: Introductionmentioning
confidence: 99%